Optimization of Agricultural Technology with Irrigation Control in Rice Plants Based on Internet of Things - Darmono; Arfin Yogatama; Khakam Ma’ruf; Yanuar Agung Fadlullah; Bagus Putra Setiyawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Agriculture in Indonesia is the cog of the country's economy. Currently Indonesia continues to strive to increase productivity in the agricultural sector, one of the efforts to increase the productivity of agricultural products is to optimize agriculture based on Internet of Things (IoT) technology using sensor devices and databases. The application of technology has advantages in terms of control systems for the irrigation process and plant nutrition. Furthermore, this research uses Research and Development (R&D) research methods or research and development methods , namely research conducted to solve problems through the development of applied technology. It is hoped that through the implementation of this innovation the process of controlling and supervising agriculture can be easily carried out so that agricultural productivity can increase and the welfare of farmers.